Diversity of weeds on bamboo seedling’s media in Bali Botanical Garden - Sutomo, Sutomo (Jurnal Biologi Udayana; Vol 23 No 1 (2019): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2019.v23.i01.p03, 2019)
In general, weeds are obnoxious plants that live in an unwanted place and have negative impact towards human, other plants and the environment. The research aimed to know the weeds species composition that composed in the growing media of Guadua chacoensis bamboo. The research was conducted in an open space of the Bali Botanical Garden nursery at an altitude of 1200 m a.s.l. The research was conducted for 3 months from July to October 2004. Results showed that as many as 28 species of weeds were found which included in 15 families. Weeds species compositions in each of the type of growing media are significantly different. In the soil media weeds comprises of Amaranthus blitum L. (Amaranthaceae) and Galinsoga parviflora Cav. (Asteraceae), in the humus media the weeds are Cyperus rotundus L. (Cyperaceae) and Gynura aurantiaca (Bl.) DC. (Asteraceae), in the cow’s feces media, the weeds is Amaranthus blitum L. (Amaranthaceae) and laslty in the KOMPENIT fertilizer media the weeds comprises of Eleusine indica (L.) Gaertn.(Poaceae), Drymaria cordata (L.) Willd. ex R. & S. (Caryophyllaceae ) and Cyperus rotundus L. (Cyperaceae).